Can Islamic crowdfunding support Indonesian Islamic Economic Masterplan? - Trisninik Ratih Wulandari; Bimo Saktiawan; Dian Ahmad (Sebelas Maret Business Review, 2021)
Islamic crowdfunding is a crowdfunding platform designed to comply with Islamic principles, a collective effort to collect/raise funds to fund projects (including startups), provide financing for personal or business, and other needs through an internet platform following Islamic principles. As a country with the largest Muslim population globally, Indonesia sees this as an excellent opportunity to support its economic development. In this regard, the purpose of this article is to find out how the Islamic Crowdfunding opportunity is an alternative solution to Islamic funding in support of the Indonesian Islamic Economic Masterplan (MEKSI). Based on data from the Ministry of Finance (Kemenkeu) through the 5th Annual Islamic Finance Conference (AIFC), Islamic Fintech assets in Indonesia grew to reach 134 billion rupiahs in June 2021, representing 3 percent of total fintech assets in Indonesia. From this data, it can be interpreted that the opportunity for Islamic Crowdfunding, which is one of the products of Islamic Fintech as alternative funding, is still very wide open. Using SWOT analysis, we find in this paper that Islamic Crowdfunding could be an alternative to Islamic funding in Indonesia. Therefore, it is expected that the government and related agencies, especially the Financial Services Authority (OJK), can take the right steps in managing Islamic crowdfunding. It is also expected that Muslims can participate in campaigning or supporting the Indonesian Islamic Economic Masterplan (MEKSI) through Islamic Crowdfunding.